STRATEGI PENGEMBANGAN PARIWISATA LOKAL (JURNAL SPASIAL, 2016)
Development of the tourism sector is expected to provide benefits to the community, because the tourism sector is one of the sectors of economic development. Tourism activity is one of the non-oil sector is expected to provide a substantial contribution to the economy Negara.Strategis pengebangan tourism in rural areas, namely by taking into account the advice and the existing infrastructure and the application of the stepping tourism. Tourism facilities can be divided into three parts, namely the principal means of tourism, tourism complementary means and means of supporting tourism. Infrastructure is divided into two parts, namely economic infrastructure and social infrastructure. And subsequent application of Sapta charm on attractions, Sapta charm which contains seven elements that define a good image of the attraction yaitunya: Safe, Orderly, Clean, Cool, Beautiful, and Suave and memories, his presence is very deeply felt important and it was time needed and not only as a basic requirement of tourists, but also as a measure to improve the quality of tourism. Pelaksananaan stepping is at the core of the program in improving the community and tourism awareness is a requirement in tourism development efforts towards the better.